Fundamentals of anatomy & physiology - Martini, Frederic H. (Pearson, 2015)
Fundamentals of Anatomy & Physiology helps you succeed in the challenging A&P course with an easy-to-understand narrative, precise visuals, and steadfast accuracy. Every chapter of the Tenth Edition includes one- and two-page Spotlight Figures that seamlessly integrate text and visuals to guide you through complex topics and processes. These highly visual presentations incorporate, for select topics, the “visual approach” that the same author team created in their Visual Anatomy & Physiology book. New Clinical Cases open every chapter and get you thinking about the chapter content in the context of a personal compelling patient story